Entrepreneurial Culture, Regional Innovativeness and Economic Growth - Sjoerd Beugelsdijk (European Regional Science Association (ERSA), 2004)
This paper presents the results of an empirical study on the relationship between entrepreneurial culture, regional rates of innovation and regional economic growth. Recent literature mainly in regional science and economic geography has emphasized the role of an entrepreneurial culture in explaining the economic success of regions. Most of these contributions are however conceptual or case-based. Building on Leibenstein's view of the entrepreneur as the `input completer' and the Austrian school in which entrepreneurial activity is attributed a central role I hypothesize that regions which can be characterized as having an entrepreneurial culture are more innovative and grow faster. I use a standard economic growth model and test this hypothesis on a sample of 54 European regions. The results confirm the importance of an entrepreneurial culture. Keywords: entrepreneurship, culture, innovation, regional economic growth JEL code: Z1, R11
Keywords: Z1; R11; 330; entrepreneurship; culture; innovation; regional economic growth